Assessment of Motor Fitness Metrics among Athletes in Different Sports: An Original Research - Md. Nasim Reza; Md. Hamidur Rahman; Muhammad Shahidul Islam; Dessalegn Wase Mola; Syed Murtaza Hussain Andrabi (OVS LLC, 2024)
Background. Motor fitness is one of the keys to athletes' success and is the initial factor mixed with game-specific technique and tactics that has an impact on game performance. All athletes should incorporate these elements into their sport and game actions. Study purpose. The aim of this study was to evaluate differences in motor fitness metrics among university-level male athletes participating in various sports. Materials and methods. Sixty (60) male athletes, ranging in age from 18 to 25 years, were selected from six different sports: Athletics, Basketball, Cricket, Football, Handball, and Volleyball. Each group consisted of 10 athletes who had competed at the inter-university level. The research focused on six key fitness metrics: agility, speed, power, arm strength, abdominal muscle strength, and cardiovascular endurance. Appropriate testing methods and instruments were used to measure these parameters. Statistical analysis, including one-way ANOVA and post hoc LSD tests, was performed to identify significant differences between the groups. A significance level of 0.05 was set for the study. Results. The results showed statistically significant differences among the groups in agility (F(5,54) = 4.776, p<0.001), speed (F(5,54) = 5.602, p<0.000), and cardiovascular endurance (F(5,54) = 3.578, p<0.007). However, no significant differences were observed for power (F(5,54) = 2.079, p>0.082), arm strength (F(5,54) = 1.368, p>0.251), and abdominal muscle strength (F(5,54) = 1.947, p>0.102). According to the post hoc (LSD) test findings, each group's agility, speed, and cardiovascular endurance parameters were compared to each other to check the significance level. Conclusions. In summary, the study has revealed that agility, speed, and cardiovascular endurance were significantly different among athletes in various sports, whereas power, arm strength, and abdominal muscle strength were not. The findings suggest that athletes and coaches should prioritize sport-specific fitness components to improve game performance.